COMPARATIVE STUDY ON THE ANTIFUNGAL ACTIVITY OF ALOE VERA LEAF AND GEL IN DIFFERENT EXTRACTS - L.TAMILARASI; R.PONNULAKSHMI; S.EZHILARASI BALASUBRAMANIAN (International Journal of Pharma and Bio Sciences, 2014)
Screening of antifungal activity of Aloe vera leaf and gel in three different solvents (aqueous, chloroform and ethanol) were carried out against selected fungal pathogens by agar diffusion method. They were tested against four fungal organisms like Aspergillus niger, Aspergillus fumigatus, Aspergillus flavus and Candida albicans. The susceptibility of the fungi to these extracts in different concentrations were compared. The highest in vitro inhibitory activity was observed with Candida albicans. Of all the three different extracts, ethanol extract of A. vera gel exhibited significant antifungal activity than the A. vera leaf extract. Hence, A. vera gel extract with ethanol can be used as an antifungal agent. The results of the present study provide a information about the role of A. vera gel for its antifungal properties.